2011
DOI: 10.1371/journal.pgen.1002028
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Deep Sequencing of Mouse Mitochondrial DNA: Mutational Patterns and Their Origins

Abstract: Somatic mutations of mtDNA are implicated in the aging process, but there is no universally accepted method for their accurate quantification. We have used ultra-deep sequencing to study genome-wide mtDNA mutation load in the liver of normally- and prematurely-aging mice. Mice that are homozygous for an allele expressing a proof-reading–deficient mtDNA polymerase (mtDNA mutator mice) have 10-times-higher point mutation loads than their wildtype siblings. In addition, the mtDNA mutator mice have increased level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
143
7
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(172 citation statements)
references
References 36 publications
20
143
7
2
Order By: Relevance
“…In addition, 8-oxo-dG's are read as dA's during replication and will result in G>A mutations as observed in the mutation pattern of Sod2 +/-mouse hearts [28]. Interestingly, this is not the case in ageing wild-type mice, which seem to accumulate mtDNA mutations caused by replication errors, thus speaking for an efficient repair of oxidative damage in most tissues [98]. Although high levels of mtDNA mutations do clearly impair OXPHOS, they do not increase ROS production [99], undermining the old hypothesis of a mitochondrial vicious circle of ROS and mtDNA damage [100].…”
Section: Mitochondrial Dna Maintenance In Cardiomyocytesmentioning
confidence: 99%
“…In addition, 8-oxo-dG's are read as dA's during replication and will result in G>A mutations as observed in the mutation pattern of Sod2 +/-mouse hearts [28]. Interestingly, this is not the case in ageing wild-type mice, which seem to accumulate mtDNA mutations caused by replication errors, thus speaking for an efficient repair of oxidative damage in most tissues [98]. Although high levels of mtDNA mutations do clearly impair OXPHOS, they do not increase ROS production [99], undermining the old hypothesis of a mitochondrial vicious circle of ROS and mtDNA damage [100].…”
Section: Mitochondrial Dna Maintenance In Cardiomyocytesmentioning
confidence: 99%
“…For example, it was shown that the mutation of the type I polymerase POLIB in Arabidopsis causes replication stress at early developmental stages and increases the amount of DSBs upon genotoxic stress treatment (Parent et al 2011). Interestingly, mutation of the mammalian mitochondrial DNA polymerase gamma has also been linked to replication stress and DSBs (Vermulst et al 2008;Ameur et al 2011). Replication-dependent DSBs are known to arise when a fork collapses or encounters a nick in the matrix DNA (Zeman and Cimprich 2014).…”
mentioning
confidence: 99%
“…The mitochondrial theory of aging suggests a role for mtDNA mutations, which can alter bioenergetics homeostasis and cellular function, in the aging process 3 . A wealth of evidence has been compiled in support of this theory 1,4 , an example being the mtDNA mutator mouse 5 ; however, the precise role of mtDNA damage in aging is not entirely understood 6,7 .Observing the activity of respiratory enzymes is a straightforward approach for investigating mitochondrial dysfunction. Complex IV, or cytochrome c oxidase (COX), is essential for mitochondrial function.…”
mentioning
confidence: 99%